Systematic Literature Review on The Utilization of Cold Chain Facilities at Several Fishing Ports in North Maluku Province - Irwan Usman; Amirul Karman; Imran Taeran; Surahman Surahman (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
This study aims to examine the existing conditions and the utilization rate of cold chain facilities at several fishing ports in North Maluku Province, in order to provide a basis for policy-making regarding the development of such facilities. This study employs the systematic literature review method. The review used the PRISMA protocol, screening 187 articles down to 14 relevant articles that were then analyzed in depth. The synthesis results show that the cold chain facilities available at the Coastal Fishing Port (CFP) Bacan, South Halmahera Regency; CFP Tobelo, North Halmahera Regency; Fish Landing Base (FLB) Goto, Tidore Islands City; and Archipelagic Fishing Port (AFP) Ternate consist of ice plants, air blast freezers (ABF), and cold storage. The utilization rate of ice plants at CFP Bacan and AFP Ternate has exceeded the optimal limit, while at FLB Goto it cannot serve fishermen’s needs because it is damaged and not operational. Meanwhile, the utilization rate of the ice plant at CFB Tobelo is not yet optimal. Furthermore, the utilization rate of air blast freezers (ABF) is not yet optimal at CFB Tobelo, FLB Goto, and AFP Ternate, whereas at CFP Bacan the utilization of ABF has exceeded the optimal limit. The utilization rate of cold storage at CFP Bacan, CFB Tobelo, and FLB Goto is not yet optimal, while the utilization rate of cold storage at AFP Ternate has exceeded the optimal limit.